Foods of Pakistan - Sheen, Barbara (Detroit : Gale Cengage Learning, 2011)
Describes the foods, cooking traditions, customs, eating habits, and ingredients of Pakistani cooking, and includes recipes for chana dal, raita, and seviyan.
Chapter 1. An Artful Blend -- Chapter 2. A Cultural Exchange -- Chapter 3. Teas and Treats -- Chapter 4. Celebrating with Food.
Includes index.
Keywords: COOKING, PAKISTANI -- JUVENILE LITERATURE